Surgical Non-Regenerative Treatments for Peri-Implantitis: a Systematic Review - Ausra Ramanauskaite; Povilas Daugela; Ricardo Faria e Almeida; Nikola Saulacic (eJournal of Oral Maxillofacial Research, 2016)
Objectives: The purposes of the present study were 1) to systematically review the literature on the surgical non-regenerative treatments of peri-implantitis and 2) to determine a predictable therapeutic option for the clinical management of peri-implantitis lesions.